Effects of the Chalcogenide Identity in N‐Aryl Phenochalcogenazine Photoredox Catalysts. Issue 17 (8th July 2022) - Corbin, Daniel A.; Cremer, Christopher; Puffer, Katherine O.; Newell, Brian S.; Patureau, Frederic W.; Miyake, Garret M.
Abstract: Phenochalcogenazines such as phenoxazines and phenothiazines have been widely employed as photoredox catalysts (PCs) in small molecule and polymer synthesis. However, the effect of the chalcogenide in these catalysts has not been fully investigated. In this work, a series of four phenochalcogenazines is synthesized to understand how the chalcogenide impacts catalyst properties and performance. Increasing the size of the chalcogenide is found to distort the PC structure, ultimately impacting the properties of each PC. For example, larger chalcogenides destabilize the PC radical cation, possibly resulting in catalyst degradation. In addition, PCs with larger chalcogenides experience increased reorganization during electron transfer, leading to slower electron transfer. Ultimately, catalyst performance is evaluated in organocatalyzed atom transfer radical polymerization and a photooxidation reaction for C(sp 2 )−N coupling. Results from these experiments highlight that a balance of PC properties is most beneficial for catalysis, including a long‐lived excited state, a stable radical cation, and a low reorganization energy. Abstract : Atom transfer : This work explores the effect of the chalcogenide identity in phenochalcogenazine photocatalysts for small molecule photooxidations and polymer synthesis by organocatalyzed atom transfer radical polymerization. Notably, increasing the size of the chalcogenide in these photocatalysts results in greater reorganization energy penalties during electron transfer as well as destabilized radical cations, slowing electron transfer and possibly leading to photocatalyst degradation, respectively.